THE EFFECT OF LEVERAGE, LIQUIDITY, AND SALES GROWTH ON PROFITABILITY FOR MANUFACTURING COMPANIES LISTED ON THE BEI: 2016-2023 PERIOD - Amrullah, Muhamad; Nadhiroh, Ulfa; Rohmah, Yushardani; Ningtyas, Mega Noerman (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study analyzes the effect of leverage, liquidity, and sales growth on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2016- 2023. Secondary data is taken from the company's annual financial statements, with independent variables of leverage (debt to equity ratio), liquidity (current ratio), and sales growth, as well as the dependent variable of profitability (return on assets/ROA). The analysis method used is multiple linear regression. Based on the results of the study, it is known that DER, and Sales Growth have no significant effect on the profitability of cigarette sub-sector manufacturing companies listed on the IDX during the period 2016 to 2023 as measured by ROA and Current Ratio has a significant effect on the profitability of cigarette sub-sector manufacturing companies listed on the IDX during the period 2016 to 2023 as measured by ROA. The results of the study are expected to provide an understanding of the factors that influence the profitability of manufacturing companies in Indonesia and useful information for stakeholders in making investment and financial management decisions.